Hemoglobin response to iron folate supplementation and associated factors among pregnant women attending public hospitals in Addis Ababa, Ethiopia: a longitudinal quasi-experimental study - Admass, Zeleke Endalew; Gessesse, Abraham Dessie; Ayalsew, Haimanot Andualem; Abate, Habtemariam Mulugeta; Leminie, Abebaye Aragaw; Wondimu, Diresibachew Haile (Frontiers in Public Health, 2025)
BackgroundIron-folate supplementation is a common recommended strategy for reducing the incidence of anemia in pregnant women. However, studies on the hemoglobin response to iron folate supplementation and factors associated with the effectiveness of the intervention in developing countries, including Ethiopia, are limited and requires further investigation.ObjectiveThis study aimed to assess the hemoglobin response to iron folate supplementation and associated factors among pregnant women attending public hospitals in Addis Ababa, Ethiopia.MethodsA quasi-experimental longitudinal study was conducted in public hospitals in Addis Ababa between May 1, 2023, and March 30, 2024. A total of 410 participants were selected via systematic random sampling. The data collection methods included participant interviews, medical record reviews, laboratory tests, and anthropometric assessments. Statistical analyses were carried out via SPSS Version 27. Descriptive statistics were used to describe the profile of the study participants. A p value of less than 0.05 was considered statistically significant. Logistic regression analysis was performed, and adjusted odds ratios (AORs) with 95% confidence intervals (CIs) were calculated to identify significant associations.ResultsA total of 59.3% of pregnant women exhibited an inadequate hemoglobin response to iron-folate supplementation, and 17% remained anemic despite supplementation. Early ANC booking (AOR = 3.9, 95% CI: 2.4–4.2), iron-folate intake for more than 2 months (AOR = 2.6, 95% CI: 1.6–4.2), adequate dietary diversity (OR = 3.4, 95% CI: 2.1–5.6), and primiparity (OR = 2.4, 95% CI: 1.4–4.2) were significantly associated with having an adequate hemoglobin response.ConclusionResults of this study showed that majority of the pregnant women living in Addis Ababa region demonstrated an in-adequate hemoglobin response to iron-folate supplementation. Early timing of antenatal care, prolonged iron-folate intake, primiparity, and adequate dietary diversity are linked to adequate hemoglobin response. Addressing these key factors could help reduce the burden of anemia during pregnancy and improve maternal and fetal health outcomes.